A staggered local damage model for fracture analysis in bi-material structures - Pham, Manh Van; Nguyen, Minh Ngoc; Bui, Tinh Quoc (Vietnam Journal of Mechanics, 2024)
This article is devoted to extension of the recently developed enhanced local damage model for failure prediction in bi-material structures. Compared to non-local models, the enhanced local model offers lower computational cost while the inherent mesh-dependency issue is treated. By defining equivalent strain based on the bi-energy norm concept and Mazars’s criterion, which considers both tensile and compressive strain components, the model aligns with the behavior of quasi-brittle materials. The state of material point is indicated by a damage parameter, ranging from 0 to 1, to represent the evolution from being fully intact to complete failure. An efficient staggered scheme is introduced, in which the equilibrium equation and the update of damage parameter are decoupled. The proposed model is validated with a series of three-point bending experimental tests on PMMA/Al6061 specimens reported by Lee and Krishnaswamy (2000). Good agreement is observed between the proposed model and experimental data, as well as numerical results from other authors, in crack path prediction.